In the shadow of asset security: Corporate social responsibility Programme by the greater Nile petroleum operating company (GNPOC), Republic of Sudan - Ghazali, Z. (Universiti Putra Malaysia, 2014)
This paper reports the findings of a study on the rationale for the provision of health services projects implemented by the Greater Nile Petroleum Operating Company (GNPOC), Sudan. The study was based on interviews with the related personnel in GNPOC, community leaders and patients. The interviews are complemented by observations made during field work on the various community development projects that have been implemented. It highlights the company's Corporate Social Responsibility (CSR) initiatives that have been over-shadowed by asset security mitigation concerns. While maintaining conventional security based on the use of paramilitary and security forces, GNPOC also initiated community development projects in the host communities. The objective was to foster a positive perspective among host communities of the company's effort on wealth sharing and to "win the hearts and minds" of the communities in order that they might protect the company's assets as their own. The paper concludes that the CSR initiatives by GNPOC are 'security driven' rather than spreading the benefits to other communities away from the oil pipeline. Â© Universiti Putra Malaysia Press.